Explore BrainMass

Explore BrainMass

    Variables

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Please show me how to convert 2 equations:
    ab + cd + ef = 0
    bg + dh + fj = 0

    into 3 equations:
    b / (cj - eh) = d / (eg - aj) = f / (ah - cg)

    © BrainMass Inc. brainmass.com March 4, 2021, 5:56 pm ad1c9bdddf
    https://brainmass.com/math/algebra/convert-two-variables-19384

    Solution Preview

    We will prove that, if
    ab + cd + ef = 0 (1)
    bg + dh + fj = 0 (2)
    then
    b / (cj - eh) = d / (eg - aj) = f ...

    Solution Summary

    This shows how to rearrange variables to turn two equations into three equations.

    $2.19

    ADVERTISEMENT